Oronoque, Norton County - Field, Samuel (Kansas State University, The Chapman Center for Rural Studies, 2015)
This is the story of Oronoque, a small Kansas town in Norton County that once thrived and had importance. Western Kansas is often overlooked, but its history should not be forgotten. This study includes newspaper articles, photographs, and an informal interview.
Samuel Field, “Oronoque, Norton County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/155.
Keywords: Oronoque; Norton County; R.S. Palmer; Leota Township; Clarence Huff; Burlington Railroad